Hypermethylation and increased expression of the DRD2 gene in schizophrenia - Lili Qing; Tiantian Zou; Wensa Yin; Run Wu; Tiantian Cheng; Haodi Yuan; Chen Zhou; Xuanyu Chen; Jia Wang; Ting Yang; Liping Hu; Linlin Liu; et al. (BMC Psychiatry)
Abstract Background Schizophrenia (SCZ) is one of the most serious mental disorders, and dysfunction of the dopamine system is a key pathological hypothesis for SCZ. The DRD2 gene is a risk gene for SCZ, and its methylation is also considered an important marker of SCZ. Among methylation sites of A total of 21 CpG sites were detected2, the CpG island upstream of exon 1 has been the most commonly studied. To our knowledge, CpG islands in other regions upstream of the start codon have not been studied. Methods MethylTarget was used to assess the methylation of 52 CpG sites in three regions of DRD2 exon 1 and intron 1, and ELISA was used to measure DRD2 protein levels. Results The methylation level of DRD2 as a whole and in the three assessed regions was significantly greater in the SCZ group than in the control group, and 26 of 52 CpG sites were significantly hypermethylated. When patients were divided by sex, 22 CpG sites with significant differences were identified in males, whereas only 2 CpG sites were identified in females by t test. After multiple testing correction, the statistical significance was attenuated for some loci. DRD2 expression in SCZ patients was lower than that in the control group. Conclusions These results suggest that hypermethylation and low expression of the DRD2 gene may be related to SCZ risk.